2018
DOI: 10.1038/s41598-018-32824-1
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell Imaging of Bioorthogonally Labelled Proteins Generated With a Single Pyrrolysine tRNA Gene

Abstract: Genetic code expansion enables the incorporation of non-canonical amino acids (ncAAs) into expressed proteins. ncAAs are usually encoded by a stop codon that is decoded by an exogenous orthogonal aminoacyl tRNA synthetase and its cognate suppressor tRNA, such as the pyrrolysine pair. In such systems, stop codon suppression is dependent on the intracellular levels of the exogenous tRNA. Therefore, multiple copies of the tRNAPyl gene (PylT) are encoded to improve ncAA incorporation. However, certain application… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…We began by testing the applicability of bioorthogonal labeling via GCE for single molecule imaging by using EGFR, a wellstudied receptor that has been previously labeled via GCE, as a benchmark. 16 To this end, EGFR was mutated to carry a TAG codon at the previously published labeling site, Leu 128, and cloned into a single expression vector that encodes the cognate pair of tRNA cua :tRNA-synthetase 17,18 (Fig. S1a †).…”
Section: Resultsmentioning
confidence: 99%
“…We began by testing the applicability of bioorthogonal labeling via GCE for single molecule imaging by using EGFR, a wellstudied receptor that has been previously labeled via GCE, as a benchmark. 16 To this end, EGFR was mutated to carry a TAG codon at the previously published labeling site, Leu 128, and cloned into a single expression vector that encodes the cognate pair of tRNA cua :tRNA-synthetase 17,18 (Fig. S1a †).…”
Section: Resultsmentioning
confidence: 99%
“…In all the above‐mentioned examples, the unAA was incorporated at the extracellular regions of the protein and labeling was performed using cell‐impermeable Tet‐Fl‐dyes, thus avoiding the relatively high background levels associated with the technique (see subsection The click reaction, below). After further optimization, the GCE‐based labeling technique was successfully applied for intracellular labeling, and various intracellular components—including intermediate filaments, microtubules, intracellular vesicles, the PM, lysosomes, and the endoplasmic reticulum—were labeled and imaged in live mammalian cells [22,24,35–38]. Here, too, small proteins that could not be labeled using protein tags were successfully labeled and imaged.…”
Section: What Has Been Done With It?mentioning
confidence: 99%
“…[65] Furthermore, whereas most researchers would argue that more tRNA is better, one study reported that too much tRNA can lead to problems, such as background labelling in fluorescence microscopy studies. [66] This means that depending on the application, it is necessary to determine the optimal amount of both tRNA and aaRS. As discussed earlier, the ratio between the tRNA and aaRS also needs to be taken into account, [58] otherwise, tRNA might be sequestered by the aaRS.…”
Section: Trna Stability and Aars/trna Ratiomentioning
confidence: 99%
“…Recent studies have focused on making more‐stable, rationally designed tRNAs for the PylRS/tRNA system [65] . Furthermore, whereas most researchers would argue that more tRNA is better, one study reported that too much tRNA can lead to problems, such as background labelling in fluorescence microscopy studies [66] . This means that depending on the application, it is necessary to determine the optimal amount of both tRNA and aaRS.…”
Section: Challenges Associated With Genetic Code Expansion and Outlookmentioning
confidence: 99%